Political Dynamics and Influence on Tourism Development in Chitwan - Ishwori Prasad Kandel, (Kaumodaki: Journal of Multidisciplinary Studies, 2025)
This study explores the influence of political dynamics and policies on tourism development in Chitwan, Nepal. Chitwan, known for its rich natural and cultural heritage, has faced opportunities and challenges in its tourism sector due to its complex political dynamics. This study uses a qualitative research approach to examine how historical events, governance, and socio-political factors have shaped tourism development, drawing on secondary data from historical documents, reports, and local archives. Additionally, informal interviews with 75 respondents, including both, domestic and international tourists, offer practical insights into the political influences on tourism. Findings indicate that while Chitwan’s tourism sector has benefited from its cultural diversity and natural beauty, it is also significantly impacted by political instability, poor infrastructure, and security challenges. Insufficient policing, high-tech security, and political unrest have hindered its potential. The study highlights the need for improved governance, infrastructure development, and a more stable political environment to promote sustainable regional tourism. This research contributes valuable insights for policymakers and stakeholders aiming to enhance the tourism industry in Chitwan while addressing political challenges that affect its growth.